EFEK VARIETAS DAN DOSIS PUPUK KANDANG TERHADAP KOMPONEN HASIL DAN HASIL MENTIMUN (Cucumis sativus L.) - Bahri, Saiful -; Patola, Efrain - (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2011)
Abstract The purpose of this research are (1) to known the effect of variety to yield component and yield of cucumber, (2) to known influence the dosage of manure to yield component and yield of cucumber, and (3) to known the effect of interaction between the variety and dosage of manure to yield component and yield of cucumber The research compiled factorially use Randomized Completely Block Design (RCBD) which consist of 2 factors and 3 replications. Factor 1 is variety by 3 levels, and factor 2 is the dosage of goat dirt cage manure by 4 level. The result of the research, are: (1) Variety of Mercy F1 give the effect better to the yield component and the yield, that is the number of fruit per plant, length of fruit, weight each fruit, weight of fruit per plant, and cucumber productivity. The average productivity of Mercy F1 is 58.73 t / ha., (2) the effect of dosage of goat dirt cage manure is non significant to the yield component and the yield of cucumber, and (3) the effect of interaction between variety with manure dosage of goat dirt cage is non significant to the yield component and the yield of cucumber Key word : variety, manure, yield, and cucumber